2013
DOI: 10.1016/j.actatropica.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of extracts from three Vitex plant species on Anopheles gambiae s.s. (Diptera: Culicidae) larvae

Abstract: Acetone and methanol extracts of different parts of three Vitex species (leaves and stem bark of Vitex trifolia, leaves, stem bark and root bark of Vitex schiliebenii and stem and root bark of Vitex payos) were evaluated for their potential to control Anopheles gambiae Giles s.s. larvae (Diptera: Culicidae). The extracts gave different levels and rate of mortality of the larvae. Some (methanol extract of V. trifolia leaves, acetone extracts of stem bark and leaves of V. schiliebenii, acetone extract of root ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Studies carried out by Nyamoita et al, [41], Nathan et al, [45] and Nathan et al, [46] reported that in addition to their lethality, the secondary metabolites of the botanicals used resulted in protracted larval phase, disrupted growth and malformation of the exoskeleton. Although there was no elongation of gut as observed in [29] and [47], incomplete melanization process was observed in larvae and some pupae examined under light microscopy (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out by Nyamoita et al, [41], Nathan et al, [45] and Nathan et al, [46] reported that in addition to their lethality, the secondary metabolites of the botanicals used resulted in protracted larval phase, disrupted growth and malformation of the exoskeleton. Although there was no elongation of gut as observed in [29] and [47], incomplete melanization process was observed in larvae and some pupae examined under light microscopy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The bioassays were conducted in accordance with the World Health Organization guidelines for testing larvicides [40] and adopted by Nyamoita et al, [41]. Crude methanolic extract (250 mg, 125 mg, 50 mg and 25 mg) was separately dissolved in 1 ml of analytical grade ethanol (Fisher Scientific, Loughborough, UK) and diluted with 499 ml of distilled water to make a 500 ml stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…The morphogenetic larvae-pupae developmental effects and decreased survival may be due to dysregulation of juvenile hormone in the mosquito by the M. koenigii phytochemicals, as evidenced by documented impact of phytochemicals in An. gambiae (Lee et al, 2015;Nyamoita et al, 2013) and other insects (Tusun et al, 2017), and/or midgut damage as observed in Culex quinquefasciatus larvae exposed to Garlic Vine extracts (Granados-Echegoyen et al, 2014;Procópio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Extracts from Vitex trifolia have been shown to disrupt An. gambiae larval growth (Nyamoita et al, 2013) and those from Turraea abyssinica are both larvicidal and adulticidal to An. gambiae (Owino et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a comparative in vivo study on the effects of extracts from three Vitex species on A. gambiae s.s. larvae at concentrations ≤ 50 ppm and 24 h time interval, found significant potency in the methanol extract of V. trifolia leaves, acetone extracts of V. schiliebenii stem bark and leaves, and acetone extract of V. payos (Lour.) Notably, V. schiliebenii and V. payos extracts demonstrated a faster mortality rate in A. gambiae s.s. larvae compared to V. trifolia , indicating their potential as effective agents for controlling A. gambiae s.s. larvae, and their promise for further investigation in mosquito control programs to combat malaria transmission ( Nyamoita et al, 2013 ).…”
Section: Biological Activities Of V Trifoliamentioning
confidence: 99%